Eksistensi Hak Tanggungan dalam Kontrak Investasi Kolektif Efek Beragun Aset (KIK-EBA) sebagai Konsep Trusts - Riky Rustam (Jurnal Hukum IUS QUIA IUSTUM, 2016)
This research aims at discussing the problems concerning KIK-EBA agreement related to the existence of personality principles and ownership status of mortgage whose trust is secured in KIK-EBA. The problem discussed is related to any legal effects of the implementation of KIK-EBA as an agreement consisting of three parties on the existence of personality principles and related to the ownership status of mortgage in the securitization mechanism used in KIK-EBA. This was a normative research whose data were collected by using a library research method. The findings conclude that KIK-EBA is not an exception of personality principle; besides, since the formal condition of agreement is not fulfilled, KIK-EBA is null and void. The ownership of mortgage in KIK-EBA is still owned by the original creditor although purchase and sale of trust has occurred as a true sale in KIK-EBA.